A Correlational Study on Taste Alterations and Quality of Life Among Cancer Patients - Wilson, S. Darsana; Nair, Chitra C.; Johns, Christy; Mathew, Christy; Joseph, Dani; DSilva, Precilla (Journal of Health and Allied Sciences NU, 2021)
Introduction One of the major problems faced by the world today is cancer. Cancer is an abnormal growth of cells. Chemotherapy, surgery, and radiation therapy are the treatment regimen for cancer. Prolonged use of chemotherapy drugs can cause different side effects such as alopecia, weight loss, sexual dysfunction, mood swings, and the most important one is taste alterations. The aim of the study is to determine the taste alterations (TAs) and quality of life (QOL) among cancer patients who have undergone three cycles of chemotherapy.Methods The approach used is descriptive survey design. The sample comprised 62 cancer patients selected by convenient sampling. The tool used was baseline proforma, University of Washington Quality of Life (UW-QOL) questionnaire version 4.1, chemotherapy-induced taste alteration scale (CiTAS).Results The majority of the patients belonged to the age group of 41 to 50 years (37.09%) among whom 40% were females. The majority of the patients were not diagnosed with any other disease (91.9%). Around 80.6% of patients reported to have sore mouth, out of whom 45.2% maintained oral care by brushing teeth. The most commonly seen type of tumor was head and neck (37.1%) whereas the tumor type genitourinary was the least seen (3.2%). The majority of the patients had stage II cancer (53.2%) and about 62% of them did not have metastasis. There is significant association with selected demographic variables and QOL (sore mouth, oral care, and tumor type). There is also a significant association with selected demographic variable and TAs, (oral care and tumor type) and there is a negative correlation between TAs and QOL.Conclusion Identification of the severity of TA helps in providing alternative measures to improve the taste buds which may help in improving the QOL.
Keywords: cancer patients; QOL; TAs